Monolayers of WxMo1−xS2 alloy heterostructure with in-plane composition variations - Zheng, Shoujun (2015)
We report the fabrication of single-crystal monolayer Wx Mo 1−xS2 alloy triangles using chemical vapor deposition method. Raman and photoluminescence property are investigated in correlation to the composition. In the monolayer triangles, the photoluminescence peak shifts continuously from 687.4 nm at the triangle center to 633.6 nm at the edge, corresponding to a switch from MoS2 to WS2 across the heterojunction. This composition-graded alloy may have interesting functions in broadband photodetection and multi-color light emission.